(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Early Chishtī malfūzāt are peppered with avowals of lamentations and hesitancy of Chishtī Shaikhs-Nizām al-Dīn Awliyā’ and Nasīr al-Dīn Mahmūd regarding their responsibility as Social actors. These discursive statements were seen as mere rhetoric in past historiography. The essay indicates that these were plotted in the texts for a crucial purpose. The mantle of leading the community conflicted with the basic ideals of mystics to renounce the world and lead a life of prayer and contemplation. It seemed a major detour on the part of the Shaikhs providing scope for condemnation by their opponents. The study illustrates that these narrative devices were employed to convey that the Saints had taken on this burdensome task unwillingly. They effectively bring out the agency of people and God in the Shaikhs taking on social responsibility. Subsequently it endorses that it was philanthropy and not worldliness behind the digression in the professed aims and actual practice of the Shaikhs. Effort is to investigate the ways in which the Shaikhs utilized these communicative tools both to silence their critics and opponents as well as validate and prioritize their functions as Social actors. The paper also examines the detailed norms of conduct that the Shaikhs prescribed for darweshes to balance their twin opposing responsibilities without falling prey to allurements.